13 Human plaque vascular smooth muscle cells show differential expression of genes associated with oxidative DNA damage. Issue 24 (24th November 2011) - Mascetti, V; Gray, K; Bennett, M
Abstract : Rationale: Oxidative DNA damage is a prominent feature of human atherosclerotic plaques. DNA damage results in vascular smooth muscle cell (VSMC) premature senescence, cell cycle arrest and apoptosis, features observed in advanced atherosclerotic plaques. Objective: To investigate key regulatory genes involved in the DNA damage response pathway in atherosclerosis, using human plaque-derived and normal aortic VSMCs under conditions of oxidative stress in vitro. Results: DNA damage and recovery was induced in normal VSMCs by treatment with tert-Butyl hydroperoxide (t-BHP), an agent that induces free radical formation. t-BHP induced robust DNA damage and recovery, as assessed by nuclear foci of damage markers P-ATM and Î 3 -H2AX, and increased comet tails, with limited cell death. A focused DNA damage gene microarray was used to determine mRNA expression levels of 84 DNA damage genes. 24/84 DNA damage-associated genes were differentially expressed more than twofold following acute oxidative stress, 19/84 genes after chronic oxidative stress, and 42/84 genes in plaque-derived VSMCs, when compared with normal human VSMCs. Notably, ATRX, GADD45G, GML, SESN1, and PPP1R15A were differentially expressed after acute and chronic oxidative stress and in plaque VSMCs. Conclusions: We have identified novel DNA damage signalling genes involved in regulating the DNA damage response, DNA repair, growth arrest and apoptosis in VSMCs exposed to oxidative stress, and in human plaque VSMCs. The overlap between genes expressed in plaque VSMCs and normal VSMCs after oxidative stress implies that their differential expression in plaque VSMCs is due to oxidative DNA damage.